Fractal model of the cracking resistance of modified polyethylene - Kozlov, G. V.; Ovcharenko, E. N.; Zaikov, G. E. (Theoretical foundations of chemical engineering, 2008)
It has been demonstrated that the fracture criterion for polyethylene samples in stress cracking tests in active media is met when the polar liquid reaches the median plane of the sample. The cracking stress resistance is accurately described within the framework of the fractal model of the transfer process in the polymers. The extremal growth of the cracking resistance is caused by structural changes due to the introduction of the finely dispersed Fe/FeO mixture and characterized by the dimensions of regions with localization of excess energy.